Prácticas; ambientes y saberes: políticas de TIC en el contexto de la educación superior colombiana. (2012)
This review article s has the purpose to show a state of the art on the academic and investigative reflection produced in the context of the relation: Higher Education and ICT policies. In order to achieve this purpose; the text is structured in three parts. Initially; a historic; brief context of the reflections; and systematization and analysis studies of the theme is accomplished. Said context was limited between the beginning of the nineties and mid 2000. At a later time; the state of the issue is registered in terms of the proposal of problems; used methodologies; obtained results and approached discussions. Finally; some considerations in relation to the found results are done.